LncRNA LINC00885 promotes bladder cancer progression by targeting the miR-98-5p/PBX3 axis: The regulatory role of LINC00885 in BLCA - Xia, Zongyu; Wang, Qin; Lu, Peng (Cellular and Molecular Biology, 2023)
Depicted as the most prevalent malignancy, bladder cancer (BLCA) associated deaths in males all around the world. Increasing evidence has uncovered that dysregulation of lncRNA is associated with the complex processes of various tumors. Although recent research concerning bladder cancer has mentioned the participation of lncRNALINC00885, the specific regulatory role of LINC00885 in BLCA hasn’t been elucidated. This study aimed to explore the regulatory role of LINC00885 in BLCA. For this purpose, qRT-PCR checked the LINC00885 expression. CCK-8, caspase-3, colony formation, and western blot (WB) experiments were carried out to intestate LINC00885 specific role in BLCA. RIP and RNA pull-down assays were used to study the regulation effect between miR-98-5p and LINC00885 (or PBX3) in BLCA. Results showed that LINC00885 was up-regulated in BLCA and promoted cell proliferation, inhibited cell apoptosis in BLCA. Molecular mechanism experiments displayed that miR-98-5p could bind to LINC00885 and PBX3. Up-regulated miR-98-5p reduced cell proliferation, and facilitated cell apoptosis in BLCA. Besides, miR-98-5p could down-regulated PBX3 expression while LINC0088 could up-regulate PBX3 in BLCA. Final rescue tests demonstrated that PBX3 deficiency reversed the miR-98-5p inhibition effect on the progression of sh-LINC00885#1-transfected cells. In conclusion, LINC00885 enhances BLCA progression by targeting the miR-98-5p/PBX3 axis, revealing that LINC00885 might serve as a novel molecular marker in bladder cancer treatment.